2017
DOI: 10.18203/2349-2902.isj20170851
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile in cases of intestinal perforation

Abstract: INTRODUCTIONIntestinal perforation is one of the most serious and frequently encountered surgical emergencies. It presents as acute abdomen and requires urgent exploratory laparotomy and corrective surgery. Out of all emergency surgical hospital admissions due to acute abdomen, the prevalence of intestinal perforation could be up to 20-40%. 1 The diagnosis is clinically obvious in many cases, though radiological confirmation is invariably sought before surgical intervention. The morbidity and mortality is adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…(Singla S et al Ersumo T et al and Utaal M et al). [6,7] Present study showed male predominance, similar results were reported by Utaal M et al and Ersumo T et al [6,7] The male preponderance can be explained by excessive intake of alcohol, smoking, tobacco chewing which is more common in males than females. Also the incidence of acid peptic diseases is more in males as compared to the females.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…(Singla S et al Ersumo T et al and Utaal M et al). [6,7] Present study showed male predominance, similar results were reported by Utaal M et al and Ersumo T et al [6,7] The male preponderance can be explained by excessive intake of alcohol, smoking, tobacco chewing which is more common in males than females. Also the incidence of acid peptic diseases is more in males as compared to the females.…”
Section: Resultssupporting
confidence: 86%
“…Our results were in concordance with the result obtained by Singla S et al and Utaal MS et al who also reported Peptic ulcer was the most common cause for gastrointestinal perforations in their respective studies. [5,7] The results of our study are in congruence with the studies Gupta et al and Vagholkar. [8,13] In their studies, Peptic perforation was the most common etiology followed by Typhoid perforations.…”
Section: Sitesupporting
confidence: 92%
See 3 more Smart Citations